PENGENDALIAN PENGGUNAAN BAHAN BAKAR MINYAK BERSUBSIDI DI KOTA SURAKARTA - Danang - Sulistianto (JI@P, 2014)
Implementation of the use control of subsidied fuel energy is based on theRegulation of Ministry of Energy and Mineral Resources Number 12 year of 2012.This research has two aims: (1) to describe the implementation of use control fuelenergy; and (2) to analyse factors affecting the obstacles the implementation ofthe use control of fuel energy in Surakarta Urban area. George C. Edward III ideawas implemented for approaching the research problems. Qualitative researchstrategy was used. Research was conducted in Surakarta Urban area. Interview,observation and library research were used to collect the data. Interctive analysismodel of data reduction, data display, and verification and conclusion drawing assuggested by Miles and Huberman is used to analyse the findings. Researchresult shows that the government has not already been well yet in controlling theuse of subsidied fuel energy. The government was still lack in socializing thepolicy. Research result also shows that the government was in a hurry insocializing their policy which impacted that the massege did not accept by the fuelenergy users clearly. It also seemed that the government was inconsistence inimplementing their policy. Unprofessional of human resources, lack of pertamaxoutlet, unclear information are factors affecting the obstacle of the implementationof the fuel energy use control. Research results also indicate that the limitationprogram of the using of fuel energy disobeyed by the government officials thatuse the official vehicles. Operators of fuel energy stations are not able toovercome this problem. Based on Energy and Mineral Resouces RegulationNumber 12 year of 2012 the its fragmentation of the bereaucracy is in charged toPertamina and fuel energy station to sell pertamax to official vehicles. BPH Migashas function as the inspector of the subsidied fuel energy using. Research resultssuggest that the quality of the sticker should be improved, sustainablesocialization must be done, and the inspection by the BPH Migas should beincreased.Key words: implementation, policy, use control, subsidied fuel energy.